Biodegradation of Petroleum Hydrocarbons by Indigenous Bacteria and Microbial Consortium under Different pH and Temperature Conditions: An HPLC Based Study - Nadia Mahdi Darweesh; Melad Khalaf Mohammed (American Journal of Biology and Natural Sciences, 2026)
Petroleum hydrocarbon biodegradation is a viable environmental conservation tool that can be used in the remediation of the oily atmosphere. In the given study, isolated native bacteria and a microbial community were tested based on their capacity to break down petroleum hydrocarbons in different pH and temperature conditions. Bacterial isolates were acquired in oil-contaminated soil and it was filtered in terms of its capability to utilize hydrocarbons. The effectiveness of biodegradation was evaluated in biomass production, optical index density, emulsification index and high performance liquid chromatography (HPLC) of the various aromatic compounds of interest. Two hundred and forty eight bacteria isolates were obtained on the oil-infested soils of which nine of them showed high ability of degrading PAH. HPLC analysis confirmed a high level of removal of the high-molecular-weight PAHs such as BaA, Chrysene, BbF, BaP, and BKF. Rhodococcus sp. provided the most efficient degradation efficiency of 88 per cent overall PAH removal with Pseudomonas putida (87 per cent) and Pseudomonas luteola (80 per cent) as the second and third best respectively. Micrococcus luteus recorded the least degradation (39%). One-way ANOVA statistical analysis showed that isolate differences were statistically significant (p < 0.05). The pH had a significant impact on PAH degradation (p < 0.05). Optimum degradation was seen at pH 7-8 where the microbial consortium performed better than the individual isolates. The consortium reported the greatest level of biodegradation in a neutral condition, which matched the highest biomass (0.294 g/L) and emulsification index (98%).Temperature also played a great role in degradation of PAH (p < 0.05). The consortium was best removed at temperatures of 30 o C, where the consortium had the best biomass (0.294 g/L) and high emulsification capacity (88 percent). Most isolates were found to be affected by thermal stress at 35C, allowing Bacillus cereus to outperform the microbial consortium, with the consortium being more metabolically cooperative and complementary in terms of enzymatic activity to effectively degrade PAH under favorable pH (7- 8) and moderate temperature (30°C). These results indicate good experimental support to the application of indigenous microbial consortia in the effective removal of petroleum hydrocarbons bioremediation.